Employing Hybrid Watermarking to Improve Email Security Against Cyber Attacks - Ahmed, Ibrahim; Awos Kh. Ali,; Mahmood S. Mahmood, (Journal of Soft Computing and Data Mining, 2025)
Email security is increasingly essential due to the growing number of IT security threats. This paper aims to assess the risks associated with emailing as a communication medium, including message interception, message loss, message content tampering, and intellectual property theft. These threats can be mitigated by employing Watermarking (WM) techniques, which have become a highly effective data protection tool. Information placed in digital content can be hidden, which can be used for document authentication and should not be exposed to unauthorized users. Hybrid watermarking is an advanced approach that can be exploited to enhance the security of an email, where both visible and invisible marks are strategically placed to protect the integrity, authenticity, and confidentiality of email content. This integration provides a robust security model that can prevent unauthorized access and identify any unauthorized use or tampering with digital content. In this paper, invisible watermarking is employed to enhance email security, complementing visible watermarks. This approach aims to strengthen email protection by increasing the likelihood of easily identifying attack attempts to compromise content or unauthorized retrieval of secure data from received emails. The performance of the selected approaches has been assessed by employing some forms of attacks, including scaling, reformatting, denoising, and noise reduction. Several metrics have been utilized to validate the quality of tested files: the cover image file's PSNR for Peak Signal to Noise Ratio, the invisible watermark file's BER and NC for Normalized Correlation.